2010
DOI: 10.1186/1744-8069-6-33
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Alternatively Spliced Isoform of the Mu-Opioid Receptor: Functional Antagonism

Abstract: BackgroundOpioids are the most widely used analgesics for the treatment of clinical pain. They produce their therapeutic effects by binding to μ-opioid receptors (MORs), which are 7 transmembrane domain (7TM) G-protein-coupled receptors (GPCRs), and inhibiting cellular activity. However, the analgesic efficacy of opioids is compromised by side-effects such as analgesic tolerance, dependence and opioid-induced hyperalgesia (OIH). In contrast to opioid analgesia these side effects are associated with cellular ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
79
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 57 publications
(87 citation statements)
references
References 61 publications
(98 reference statements)
8
79
0
Order By: Relevance
“…Morphine-dependent exacerbation of Tat neurotoxicity has been attributed to direct actions on glia . Although morphine typically acts in an inhibitory manner, an excitatory MOR-1K splice variant (Gris et al, 2010) has been described in human astroglia (Dever et al, 2014). In that study, MOR-1K was not found to be expressed by neurons, although the human neurons sampled were from undefined brain regions and did not appear to include striatal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Morphine-dependent exacerbation of Tat neurotoxicity has been attributed to direct actions on glia . Although morphine typically acts in an inhibitory manner, an excitatory MOR-1K splice variant (Gris et al, 2010) has been described in human astroglia (Dever et al, 2014). In that study, MOR-1K was not found to be expressed by neurons, although the human neurons sampled were from undefined brain regions and did not appear to include striatal neurons.…”
Section: Discussionmentioning
confidence: 99%
“…Although strongly suggestive, the complexity of the mu receptor MOR-1 gene and its splice variants (section VIII) raises a number of issues. With dozens of splice variants identified in mice, rats, and humans (Bare et al, 1994;Du et al, 1997;Pan et al, 1998bPan et al, , 1999Pan et al, , 2000Pan et al, , 2001Pan et al, , 2003Pan et al, , 2005aPasternak et al, 2004;Doyle et al, 2007b;Xu et al, 2009Xu et al, , 2011Gris et al, 2010), it is not yet clear which one(s) dimerize with delta receptors and how this affects their pharmacology.…”
Section: A Receptor Bindingmentioning
confidence: 99%
“…Originally identified in mice and located approximately 30 kb upstream of exon 1 (Pan et al, 2001), exon 11, and its splice variants have been identified in an additional eight mammalian OPRM1 genes by homologous cloning or bioinformatic searches, including rat and human (Pan et al, 2001Xu et al, 2006Xu et al, , 2009Gris et al, 2010) (section VIII). Exon 11 contains its own promoter that is distinct from the promoter responsible for generating the exon 1 variants.…”
Section: B Phylogeny and Evolutionmentioning
confidence: 99%
“…Furthermore, membrane trafficking of NMDA receptors with NR2B subunit have been shown in remifentanil induced hyperalgesia through glycogen synthase kinase-3␤ (GSK-3␤) pathway (Li et al, 2013;Yuan et al, 2013). Some studies indicated that NMDA receptor function would be enhanced after chronic morphine exposure as well as 4, 6 or 8 nM remifentanil infusion (Gris et al, 2010;Hang et al, 2011;Zhao and Joo, 2008). Therefore, the expression level, membrane trafficking and functional changes of NMDA receptors are potential mechanisms of OIH.…”
Section: Introductionmentioning
confidence: 97%